Exploration of Korean Students' Mathematics Achievement, School Climate, and Well-being in PISA 2018 Results - Seongmin Cho; Namwook Koo (Korea Society of Educational Studies in Mathematics, 2020)
PISA　was implemented in 43 countries and economics in the first assessment. But now it has become a representative international comparative study as the number of participating countries and the interest in　PISA results have increased. At the end of last year, the OECD announced the PISA 2018 results, and Korea recorded a high level of achievement, similar to the PISA 2015 results of the previous cycle. However, considering that the mean score of the PISA 2015 mathematics declined by 30 points compared to the PISA 2012 mathematics, it is necessary to interpret the PISA 2018 results by trend analysis on the percentage of the correct response and the proficiency in mathematics in addition to the comparison of the mean scores. Meanwhile, PISA provides indices of the educational context variables as well as the results of student achievement. Thus, this study outlined the results of the PISA 2018 mathematics domain, analyzed the trend of the percentage of correct answer by subcategory of mathematics framework and the results of school climate and student well-being by mathematics achievement level and also derived the implications for improving students' achievement.